CDK4/6 Inhibitors in Combination Therapies: Better in Company Than Alone: A Mini Review - Gian Luca Rampioni Vinciguerra; Gian Luca Rampioni Vinciguerra; Maura Sonego; Ilenia Segatto; Alessandra Dall’Acqua; Andrea Vecchione; Gustavo Baldassarre; Barbara Belletti (Frontiers in Oncology, 2022)
The cyclin D-CDK4/6 complexes play a pivotal role in controlling the cell cycle. Deregulation in cyclin D-CDK4/6 pathway has been described in many types of cancer and it invariably leads to uncontrolled cell proliferation. Many efforts have been made to develop a target therapy able to inhibit CDK4/6 activity. To date, three selective CDK4/6 small inhibitors have been introduced in the clinic for the treatment of hormone positive advanced breast cancer patients, following the impressive results obtained in phase III clinical trials. However, since their approval, clinical evidences have demonstrated that about 30% of breast cancer is intrinsically resistant to CDK4/6 inhibitors and that prolonged treatment eventually leads to acquired resistance in many patients. So, on one hand, clinical and preclinical studies fully support to go beyond breast cancer and expand the use of CDK4/6 inhibitors in other tumor types; on the other hand, the question of primary and secondary resistance has to be taken into account, since it is now very clear that neoplastic cells rapidly develop adaptive strategies under treatment, eventually resulting in disease progression. Resistance mechanisms so far discovered involve both cell-cycle and non-cell-cycle related escape strategies. Full understanding is yet to be achieved but many different pathways that, if targeted, may lead to reversion of the resistant phenotype, have been already elucidated. Here, we aim to summarize the knowledge in this field, focusing on predictive biomarkers, to recognize intrinsically resistant tumors, and therapeutic strategies, to overcome acquired resistance.